Clintonomics : how Bill Clinton reengineered the Reagan revolution - Godwin, Jack (AMACOM, 2009)
Political scientist Godwin presents Bill Clinton's ideas on power, strategy, and twenty-first-century statecraft from the viewpoint of the presidency. With his research involving thousands of documents and transcripts, Godwin explains that while Clinton positioned himself as the antidote for Reaganomics, his governing philosophy was the logical outcome of the Reagan Revolution. We learn of President Reagan's political influence on Clinton, including balancing the budget and welfare reform. Godwin notes that Clinton returned the country to fiscal discipline and ended big government, both principles that Reagan supported. The author seeks to illuminate the similarities between Reagan and Clinton, contending that they were separated more by political party than by political ideology. Hoping to spur debate about the legacies of these great leaders, the author states, "Clinton succeeded where Reagan failed by transcending the simplistic debate between liberals who want to expand government and conservatives who want to starve it to death. No doubt, some of Reagan's admirers will disagree." No doubt